Educação para a sustentabilidade nas instituições de ensino: um estudo sobre a gestão de resíduos sólidos e tecnologias de reciclagem - Cebinelli, Juliana Patrícia (2024)
This research aimed to conduct a comprehensive study on solid waste management in educational institutions, seeking to identify opportunities for implementing sustainable recycling practices based on what is generated in the school environment. To achieve this goal, specific objectives were established to guide the research. The methodology employed in this study involved an initial literature review focused on understanding the characteristics of urban solid waste and its related environmental impacts. Subsequently, a detailed diagnosis of the solid waste generated in a school located in the western region of Paraná was conducted. Data collection included quantifying and classifying the types of produced waste, as well as identifying consumption, generation, and disposal practices. Furthermore, a comprehensive literature review was conducted on recycling technologies for the identified solid waste, involving the evaluation of innovative technologies in the recycling field through publications from the last 10 years. As a practical part of this research, an operational procedure was developed for implementing selective waste collection in the school, based on the practices carried out and aligned with the institution's curriculum. This procedure outlined the necessary steps for effective waste separation, establishing minimal appropriate infrastructure, and creating an efficient waste management system. Additionally, environmental education actions were proposed to promote awareness and participation of the school community in selective waste collection and reducing waste generation. Regarding the waste generated in the analyzed school, organic waste was predominant, followed by paper and plastic, while smaller quantities of metal and glass were also identified. In the educational context, implementing selective collection practices becomes crucial to raise awareness and environmental responsibility among students and the school community. Furthermore, having elective courses focused on environmental education can trigger greater interest and engagement from students, enhancing their understanding of the importance of environmental preservation. These actions aim not only to implement recycling practices but also to ensure their long-term sustainability. In summary, this dissertation seeks to significantly contribute to the responsible management of solid waste in educational institutions, emphasizing the importance of recycling and environmental education to promote a more sustainable and conscious school environment.